Two-level factorial screening of microwave-assisted extraction parameters for the recovery of phenolic compounds from vernonia cinerea leaf - Alara, Oluwaseun Ruth; Nour, A. H.; Alara, John Adewole (Universiti Malaysia Pahang, 2019)
Vernonia cinerea is one of the medicinal plants with several potentials for treating different alment. In the present study. Microwave-assisted extraction (MAE) was employed in extracting phenolic compounds from this plant. However, different factors that affect this extraction method in the recovery of phenoli compounds abound, these factors need to be screened to determine actual contributing factor in order to minimize cost. Irradiation time (1-5 min), ethanol concentration (20-60% v/v), microwave power (40-80 W), extraction temperature (40-80 °C), and feed/splvent (1:10-1:18 g/mL) have been screen using the two-level factorial design for the recoveries of phenolic compounds from V. cinerea leaves. The results obtained in this study indicated that only microwave power, ethanol concentration, irritation time, and feed/solvent contributed to recoveries of total phenolic content (TPC) and total flavonoid content (TFC) from V. cinerea leaves. Thus, these factors at these ranges can further be optimized to obtain optimal yields of phenolic compounds from V. cinerea leaves.